Causal attribution to craneofacial trauma from northern patagonian Samples (República Argentina): an experimental perspective - Gordón, Florencia (2009)
In the context of assessment of the hypothesis which relates ecological changes during Medieval Climatic Anomaly (1.150-600 calendar years BP) with increasing levels of violence in Northeastern Patagonia, a particular type of trauma in the latest sample was detected. In this context, two lines of evidence are proposed: on the one hand, a bibliographic survey of the regional technology; on the other, more emphatically, the application of an experimental program which allows to make possible links between effectors and traces. The first line of evidence sheds light on the generalized and multipurpose characteristics of the toolkit of the local groups before the European population arrived. However, the presence of metallic blades since, at least the middle of XVII century, could explain the high frequency of linear depressions which characterizes latest sample. In this sense, the first results of the experimental survey, of macroscopic nature, for which long blades and heads of pigs were used as proxies, are concurrent. The recurrence of these injuries in individuals from late contexts, which latest dates are of 350 years BP, would be recording early moments of the colonial period, although later than Medieval Climatic Anomaly.